CHROMIUM SPECIATION AND MOBILITY IN A HIGH LEVEL NUCLEAR WASTE VADOSE ZONE PLUME - Zachara J.M.; Ainsworth C.C.; McKinley J.P.; Qafoku O.; Smith S.C.; Szecsody J.E.; Brown Jr.G.E.; Catalano J.G.; Warner J.A.; Traina S.J. (My University, 2004)
Radioactive core samples containing elevated concentrations of Cr from a high level nuclear waste plume in the Hanford vadose zone were studied to asses the future mobility of Cr. Cr(VI) is an important subsurface contaminant at the Hanford Site. The plume originated in 1969 by leakage of self-boiling supernate from a tank containing REDOX process waste. The supernate contained high concentrations of alkali (NaOH ≈ 5.25 mol/L), salt (NaNO3/NaNO2 >10 mol/L), aluminate [Al(OH)4− = 3.36 mol/L], Cr(VI) (0.413 mol/L), and 137Cs+ (6.51 × 10−5 mol/L). Water and acid extraction of the oxidized subsurface sediments indicated that a significant portion of the total Cr was associated with the solid phase. Mineralogic analyses, Cr valence speciation measurements by X-ray adsorption near edge structure (XANES) spectroscopy, and small column leaching studies were performed to identify the chemical retardation mechanism and leachability of Cr. While X-ray diffraction detected little mineralogic change to the sediments from waste reaction, scanning electron microscopy (SEM) showed that mineral particles within 5 m of the point of tank failure were coated with secondary, sodium aluminosilicate precipitates. The density of these precipitates decreased with distance from the source (e.g., beyond 10 m). The XANES and column studies demonstrated the reduction of 29–75% of the total Cr to insoluble Cr(III), and the apparent precipitation of up to 43% of the Cr(VI) as an unidentified, non-leachable phase. Both Cr(VI) reduction and Cr(VI) precipitation were greater in sediments closer to the leak source where significant mineral alteration was noted by SEM. These and other observations imply that basic mineral hydrolysis driven by large concentrations of OH− in the waste stream liberated Fe(II) from the otherwise oxidizing sediments that served as a reductant for CrO42−. The coarse-textured Hanford sediments contain silt-sized mineral phases (biotite, clinochlore, magnetite, and ilmenite) that are sources of Fe(II). Other dissolution products (e.g., Ba2+) or Al(OH)4− present in the waste stream may have induced Cr(VI) precipitation as pH moderated through mineral reaction. The results demonstrate that a minimum of 42% of the total Cr inventory in all of the samples was immobilized as Cr(III) and Cr(VI) precipitates that are unlikely to dissolve and migrate to groundwater under the low recharge conditions of the Hanford vadose zone.